Pengembangan Sistem Informasi Akademik Berbasis Web pada SMP Negeri 4 Rambutan - FADIAH DIYAH; Evi Yulianingsih (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Efficient and integrated academic data management is a crucial need in the digital era, especially at the Junior High School level. This study aims to develop a web-based academic information system at State Junior High School 4 Rambutan to improve the effectiveness and efficiency of overall school academic data management. The development method used is the prototype method which involves iterative interactions between developers and users through the stages of gathering needs, creating an initial prototype, evaluating by users, and refining the system until it is ready for implementation. The developed system has key features in the form of student data management, attendance, assessments, lesson schedules, and academic reports that can be accessed in real-time by the school, students, and parents. The development results show that the prototype method allows the creation of a system that is more suited to user needs, speeds up the administrative process, reduces the potential for manual errors, and increases the transparency of academic information. With an intuitive and web-based interface, this system can be accessed on various devices, providing a modern solution to support the quality of education at State Junior High School 4 Rambutan.